Beyond Reflective Practice : New Approaches to Professional Lifelong Learning. - Bradbury, Helen (Taylor and Francis, 2009)
Reflective practice has moved from the margins to the mainstream of professional education. However, in this process, its radical potential has been subsumed by individualistic, rather than situated, understandings of practice. Presenting critical perspectives that challenge the current paradigm, this book aims to move beyond reflective practice. It proposes new conceptualisations and offers fresh approaches relevant across professions. Contributors include both academics and practitioners concerned with the training and development of professionals. Definitions of reflection (which are often.